New Perspectives in the Studies on Endocannabinoid and Cannabis: Abnormal Behaviors Associate With CB1 Cannabinoid Receptor and Development of Therapeutic Application - Michihiro Fujiwara; Nobuaki Egashira (Elsevier, 2004)
Δ9-Tetrahydrocannabinol (Δ9-THC), the major psychoactive component of marijuana, induces catalepsy-like immobilization and impairment of spatial memory in rats. Δ9-THC also induces aggressive behavior in isolated housing stress. These abnormal behaviors could be counteracted by SR141716A, a CB1 cannabinoid receptor antagonist. Also Δ9-THC inhibited release of glutamate in the dorsal hippocampus, but this inhibition could be antagonized by SR141716A in an in vivo microdialysis study. Moreover, NMDA and AMPA-type glutamate receptor enhancers improved the Δ9-THC-induced impairment of spatial memory. On the other hand, Δ9-THC markedly inhibited the neurodegeneration in experimental allergic encephalomyelitis (EAE), an animal model of multiple sclerosis and reduced the elevated glutamate level of cerebrospinal fluid induced by EAE. These therapeutic effects on EAE were reversed by SR141716A. Taken together, our results demonstrate that the inhibition of glutamate release via activation of the CB1-cannabinoid receptor is one mechanism involved in Δ9-THC-induced impairment of spatial memory, and the therapeutic effect of Δ9-THC on EAE, and a Δ9-THC analog might provide an effective treatment for psychosis and neurodegenerative diseases. Keywords:: Δ9-tetrahydrocannabinol, CB1 cannabinoid receptor, glutamate, spatial memory, experimental allergic encephalomyelitis